Sustainable production of microalgal nanoparticles through green synthesis towards cancer treatment - Garlapati, Vijay Kumar; Sharma, Swati; Sharma, Deepak; Kumar, S. P. Jeevan; Jacob, Samuel; Kuila, Arindam; Gupta, Ashok Kumar; Chaudhary, Abhishek (Frontiers in Bioengineering and Biotechnology, 2025)
Nanoparticle-based treatment is one of the rapidly growing research domains in cancer treatment due to its associated structural, targeted, and stability features. The conventional (chemical and physical) nanoparticle (NP) synthesis suffers from drawbacks such as toxicity, cost, and unsustainable process methodologies, which necessitate the urgent need for sustainable green approaches to nanoparticle synthesis for envisioned cancer treatment options. The green synthesis of microalgal NPs is a promising approach for obtaining NPs for cancer treatment. As a result, this review presents the synthesis mechanism of microalgal NPs and the factors affecting their green synthesis. The mechanism of action of microalgal NPs in cancer treatment has been discussed in relation to their cytotoxic effects. The sustainability features, probable quality control regime of green-synthesized microlgal NPs, along with the prospects of incorporating synthetic biology and utilizing genetically engineered microalgae, have been highlighted in the context of cancer treatment.